MOOC development with case studies method in strategic management course for students to improve learning quality - Lylys Endarwati; Eveline Siregar; Cecep Kustandi (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2025)
How to develop MOOCs on Strategic Management courses with case studies method for master’s program students? To produce MOOCs on Strategic Management courses using the case studies method for master’s students, innovation is required in design and planning. This development research uses the research method and development by applying the ASSURE model. Quantitative data was obtained through material expert tests, learning design expert tests, and one-to-one tests. The results of this study showed that the development of MOOCs with the case study method is very feasible to apply to S-2 program students, scoring 4 out of 4. The results of the learning design expert test obtained 3.7 out of 4, declaring that it is feasible to apply to graduate students. This study attempts to help support the Sustainable Development Goals education sector so that the wider public can continue to learn throughout life through MOOCs and so that they can be a guide in developing learning MOOCs with case method studies.